Influence of expectation on sensorial shelf-life of grape pomace flour-based bread - Sant Anna, Voltaire; Baldissera, Caroline; Leães, Fernanda Leal (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2022)
The present work aimed to evaluate whether consumers’ expectations affect sensorial shelf life (SSL) of a bread added of grape pomace flour by two SSL approaches. A chemical-free vegan bread added of dried grape pomace was storage at room temperature for up to 7 days. On hundred people were asked about their expectation to try it and evaluated the breads’ softness, flavor and overall acceptance. Additionally, participants were asked whether each sample was sensorial accepted or not. SSL were estimated statistically by acceptability limit and survival analysis. Consumers with the lowest expectation are more sensitive to sensory changes over storage. Participants the with highest expectations evaluated the breads’ softness to be hedonically acceptable up to 4 days, flavor up to 5 days and globally up to 7 days. Those with the lowest expectations, liked the product’s softness and flavor up to 1 day, meanwhile overall acceptance was good throughout 2 days of storage. Consumers with slight positive expectation were sensitive to texture and flavor changes in comparison to those with high expectation, but global acceptance were similar. SSL estimation based on survival analysis was close to 7 days, and expectation did not affect the probability of consumers reject the product. Grape residue-based products are eco-innovations for food industries and SSL has never been reported in literature for this kind of product, which is essential to proper launch it in the market.